Simultaneous detection of Cu2+ and Cr3+ by a simple Schiff-base colorimetric chemosensor bearing NBD (7-nitrobenzo-2-oxa-1, 3-diazolyl) and julolidine moieties. Issue 35 (1st September 2016) - Lee, Seong Youl; Bok, Kwon Hee; Kim, Jin Ah; Kim, So Young; Kim, Cheal
Abstract: A new NBD (7-nitrobenzo-2-oxa-1, 3-diazolyl) and julolidine-based chemosensor1 was designed and synthesized as a colorimetric chemosensor for Cu 2+ and Cr 3+ . The presence of Cu 2+ and Cr 3+ led to distinct visible color changes from violet to yellow and blue, respectively, in aqueous solution. To examine the binding mechanisms of1 with Cu 2+ and Cr 3+, UV–vis spectroscopy, ESI-mass spectrometry analysis and DFT calculations were conducted. The detection limits for the analysis of Cu 2+ and Cr 3+ ions were found to be 0.36 μM and 0.59 μM, respectively. Practically, sensor1 functioned as a visible test strip for Cu 2+ and Cr 3+ . Moreover, the sensing abilities of1 for Cu 2+ and Cr 3+ were successfully carried out in real water samples. Therefore, sensor1 can be employed as a practical colorimetric chemosensor for detecting both Cu 2+ and Cr 3+ . Graphical abstract: